Breeding beef cattle for an extended productive life: Evaluation of selection criteria in the Retinta breed - Morales, R. (2017)
We characterized genetically the longevity and the productive life of beef cows considering three different traits: length of true life (LTL), the length of productive life (LPL) and a number of calvings (NC), in the Retinta breed. Data considered in the analysis were collected in 30 Spanish herds and consisted of 3,187 cows born between 1993 and 2013: 1,802 cows had complete information while 1,385 cows had censored information. Pedigree information accounted for 7,359 individuals and the genetic evaluation was performed under an animal model using the Weibull proportional hazard model for survival analysis. Results indicated that cow effects (age at first calving, herd, season-year of cow birth), as well as some calf effects (breed group, season-year of birth), were significant (P<0.05) for all traits; however, sex of calves did not affect the traits. The low heritabilities obtained for LTL and LPL (0.14 ± 0.01 and 0.14 ± 0.01 respectively) and modest heritability for NC (0.30 ± 0.01), suggest that a higher response to selection can be expected for NC than for LTL and LPL.